Glucocorticoid-induced leucine zipper (GILZ) antagonizes TNF-α inhibition of mesenchymal stem cell osteogenic differentiation. - Linlin He (Public Library of Science (PLoS), 2012)
Tumor necrosis factor-alpha (TNF-α) is a potent proinflammatory cytokine that inhibits osteoblast differentiation while stimulating osteoclast differentiation and bone resorption. TNF-α activates MAP kinase pathway leading to inhibition of osterix (Osx) expression. TNF-α also induces the expression of E3 ubiquitin ligase protein Smurf1 and Smurf2 and promotes degradation of Runx2, another key transcription factor regulating osteoblast differentiation and bone formation. We showed previously that overexpression of glucocorticoid (GC)-induced leucine zipper (GILZ) enhances osteogenic differentiation of bone marrow mesenchymal stem cells (MSCs). We and others also showed that GILZ is a GC effecter and mediates GC anti-inflammatory activity. In this study, we asked the question whether GILZ retains its osteogenic activity while functioning as an anti-inflammatory mediator. To address this question, we infected mouse bone marrow MSCs with retroviruses expressing GILZ and induced them for osteogenic differentiation in the presence or absence of TNF-α. Our results show that overexpression of GILZ antagonized the inhibitory effects of TNF-α on MSC osteogenic differentiation and the mRNA and protein expression of Osx and Runx2, two pivotal osteogenic regulators. Further studies show that these antagonistic actions occur via mechanisms involving GILZ inhibition of TNF-α-induced ERK MAP kinase activation and protein degradation. These results suggest that GILZ may have therapeutic potential as a novel anti-inflammation therapy.